2018
DOI: 10.1101/331900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative genomic analysis of early neurogenesis reveals a temporal genetic program for differentiation and specification of preplate and Cajal-Retzius neurons

Abstract: 28Background: Neurogenesis in the developing cerebral cortex begins with the generation of the 29

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…We previously performed RNA sequencing (RNA-seq) analysis of cortical NSPCs from the Ebf2-EGFP mouse embryos (Figure 1A)(Chuang et al, 2011; Li et al, 2019a). Among the genes that are differentially expressed in E11.5 cortical NSPCs (with the expression level of FPKM > 1 and fold change > 2 compared with that in the preplate neurons), we identified 25 NSPC-enriched lncRNAs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We previously performed RNA sequencing (RNA-seq) analysis of cortical NSPCs from the Ebf2-EGFP mouse embryos (Figure 1A)(Chuang et al, 2011; Li et al, 2019a). Among the genes that are differentially expressed in E11.5 cortical NSPCs (with the expression level of FPKM > 1 and fold change > 2 compared with that in the preplate neurons), we identified 25 NSPC-enriched lncRNAs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…An unexpected feature is that the transcriptome of the β-catenin GOF ChP has some components that fit with a CR cell-like profile, such as Ebf2, Jph3, Reelin, Slit1 53 and others that fit with a medial cortical/hippocampal-like profile (Lef1, Prox1, Wif1), in addition to an array of cortical neuroepithelial or postmitotic neuronal markers (Supplementary Table 1). While it is not possible to delineate whether there is a heterogenous population of CR-like, hippocampal-like, and cortical neuron/neuronal progenitor-like cells in the β-catenin GOF ChP using bulk RNAseq, it appears that the overall picture is one of mixed transcriptomic signatures, at least at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…Having observed CR cell abnormalities in Lmx1a mutants (Fig. 2D-E'), we studied whether our newly identified Lmx1a downstream targets include genes associated with CR cells, taking advantage of recently identified datasets of genes enriched in CR cells (Franzén et al, 2019;Li et al, 2021). 11 known CR cell-enriched genes were downregulated (Car10,Lhx1,Trp73,Cntnap2,Reln,Cdkn1a,Chst8,Spock1,Akap6,Cacna2d2,Tbr2) and six -were upregulated (Tmem163,Sema6a,Lhx5,Lingo1,Edil3,MAPK8) in the CH of Lmx1a-/-embryos (green dots in Fig.…”
Section: Reduced Exit Of Ch Progenitors From the Cell Cycle And Compr...mentioning
confidence: 99%
“…1K-M): the first segment (labeled as DMS) was between the DNe and FDJ, the second was along the surface of the FDJ, and the third was in the DG (Cai et al, 2018). (Franzén et al, 2019;Li et al, 2021) are shown in green; the only previously identified Lmx1a target in the CH, Cux2 (Fregoso et al, 2019), is shown in red.…”
Section: Lmx1a Protein)mentioning
confidence: 99%